#TITLE_ALTERNATIVE# - SOENARYO (NIM : 13706043); Dosen Pembimbing : Dr. I Made Arcana, TIRTO
Battery of lithium ion polymer is being widely researched because it is safer to use than any other batteries. Due to the low in conductivity of lithium ion and the need to keep the environment clean, many researchers carry out researches about battery membrane made from natural polymers. The natural polymers which are potentially researched in Indonesia are chitosan and sodium alginate since the raw materials of chitosan and sodium alginate are very abundant. In this research, chitosan was isolated from shrimp shells and sodium alginate was isolated from brown algae. The functional groups of the polymers were analyzed by using FTIR (Fourier Transform Infra Red) spectroscopy. The degree of deacetylation of chitosan was determined by using infrared spectroscopy method, and the molecular weight of the polymers was determined by using viscometry method. In this work, yield of chitosan obtained was 24.03 %, alginic acid was 21.24 %, and sodium alginate from its acid was 109.88 %. The degree of deacetylation of isolated chitosan was 66 %, and its molecular weight was 6.48x105 grams/mole, while the molecular weight of isolated sodium alginate was 1.36x104 grams/mole. The preparation of membranes was carried out by casting of polymers solution. The membranes were characterized by FTIR spectroscopy for the analysis of functional groups, XRD (X-ray Diffractometry) for crystallinity analysis, SEM (Scanning Electron Microscopy) for analysis of membrane morphology, tensile testing for mechanical strength analysis, TGA/DTA (Thermal Gravimetric Analysis / Differential Thermal Analysis) for thermal stability analysis and EIS (Electrochemical Impedance Spectroscopy) for the analysis of specific ion conductivity. The changes in absorption bands of FTIR spectra and in degradation temperatures indicate the presence of bond between carboxylate groups of sodium alginate and amine groups of chitosan. The blending of polymers between chitosan and sodium alginate could not form a homogeneous membrane. Based on the analysis of mechanical property and conductivity, the optimum membrane was sodium alginate/ lithium acetate dihydrate membrane with tensile strength of 27.96 MPa, tensile strain of 46,8% and specific ion conductivity of 7.94x10-3 S/m, although the initial degradation temperature of this membrane was about 197oC.